Improving water stability of extrudate feed for C. porosus using Sodium alginate : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science major in Animal Science at Massey University, Manawatū, New Zealand - Francis, Magdalene (Massey University, 2014)
The extrudate sausage-pellet feed that is used currently to feed farmed C. porosus disintegrates on contact with water, which leads to leaching of nutrients and results in approximately 50% of feed being wasted. The objective of this study was to ascertain if Na alginate could be used to improve feed stability in water and then examine its effects on animal digestibility. The approach first looked at in vitro laboratory experiments to examine optimal conditions for Na alginate use. The second phase then applied those findings on-farm in a digestibility trial to measure if Na alginate affected digestion. Acceptance of feed containing Na alginate by crocodiles was also observed. In the laboratory, a new diet was replicated from the ‘MHCF 2012/2 Fine’ feed formulation obtained from Mainland Holdings Crocodile Farm (MHCF) and had three sodium alginate products (Protanal XP 3639, Manucol DM and Kimica) added separately at 1.7 and 3.3% (as-fed). Each of these was cross-linked with either CaCaO3 or CaCl2 at 1.9% w/w rate. Feed was subjected to sensory evaluation and water stability measurements. For sensory evaluation, the diets were assessed by physical observation of their texture by sight and by feel and scores were given for traits including cohesiveness, viscosity, adhesiveness, and wetness. For water stability, a sample of feed for each alginate product, alginate level, and Ca source (15-30g) was collected and subjected to water submersion for 18-24 hours and then was oven dried. Its dry matter recovery (DMR) was calculated as a proportion of the DM remaining after water immersion to the initial DM added to the water. Reaction with CaCO3 resulted in greater DMR (80.68% DMR; P < 0.05) compared with CaCl2 (16.08% DMR). There was a greater than 10-fold increase in DMR when Na alginate was used with CaCO3 compared to the control (86.7% vs. 6.2% DMR), however there were no differences in DMR among all Na alginates and inclusion levels with CaCO3. Therefore, the least expensive Na alginate product at the lower inclusion level with CaCO3 was recommended for use on-farm and in the digestibility experiment. For the on-farm digestibility experiment, ten juvenile crocodiles (2.2-2.4 years of age, 1.2-1.9 kg BW) were chosen from farm raised stocks and fed the extrudate chicken by-product-based diets with and without 1.4% sodium alginate and 1.9% CaCO3 added. The percentage composition of sodium alginate was reduced due to increase in component of other ingredients (except sodium alginate) to meet tha capacity of the processing machine. Animals were fed 2% BW for 12 d, with faeces collected the last 5 d. Animals were then slaughtered and digesta sampled from the ileum. Acid insoluble ash was used an internal marker. There were no effects of alginate on faecal digestibility of DM ( 0.350 vs 0.664, SE = 0.101) and N (0.249 vs 0.556, SE = 0.15) as well as ileal digestibilities for AA, DM, OM and N between the two diets (DM = 0.360 vs 0.410, SE = 0.146; OM = 0.396 vs 0.468, SE = 0.128; N= 0.558 vs 0.650, SE=0.122), except OM and energy faecal digestibilities were greater with Na alginate (OM = 0.392 vs 0.698, SE = 0.091; energy = 0.444 vs 0.722, SE = 0.083) These results indicate there were no deleterious effects of alginate on digestibility of nutrients in C. porosus. In conclusion, this study showed that Na alginate had the potential to effectively reduce feed wastage and cost by preventing the feed from disintegrating and dissolving on contact with water. Furthermore, Na alginate did not interfere with feed digestion in C. porosus.
Keywords: Crocodiles; Feeding and feeds; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production::Animal nutrition and management